Immunoliposomes: A review on functionalization strategies and targets for drug delivery - Eloy, Josimar O. [UNESP]; Petrilli, Raquel [UNESP]; Trevizan, Lucas Noboru Fatori [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2017)
Nanoparticles, especially liposomes, have gained prominence in the field of drug delivery for the treatment of human diseases, particularly cancer; they provide several advantages, including controlled drug release, protection of the drug against degradation, improved pharmacokinetics, long circulation, and passive targeting to tumors and inflammatory sites due to the enhanced permeability and retention effect. The functionalization of liposomes with monoclonal antibodies or antibody fragments to generate immunoliposomes has emerged as a promising strategy for targeted delivery to and uptake by cells overexpressing the antigens to these antibodies, with a consequent reduction in side effects. In this review, we address functionalization strategies for the non-covalent and covalent attachment of monoclonal antibodies and their fragments to liposomal surfaces. The main reaction occurs between the sulfhydryl groups of thiolated antibodies and maleimide-containing liposomes. Furthermore, we explore the main targeting possibilities with these ligands for the treatment of a variety of pathologies, including HER2- and EGFR-positive cancers, inflammatory and cardiovascular diseases, infectious diseases, and autoimmune and neurodegenerative diseases, which have not previously been reviewed together. Overall, many studies have shown selective delivery of immunoliposomes to target cells, with promising in vivo results, particularly for cancer treatment. Although clinical trials have been conducted, immunoliposomes have not yet received clinical approval. However, immunoliposomes are promising formulations that are expected to become available for therapeutic use after clinical trials prove their safety and efficacy, and after scaling issues are resolved.
Keywords: Functionalization; Immunoliposomes; Liposomes; Monoclonal antibodies; Targeted delivery